2006
DOI: 10.2340/00015555-0153
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Adverse Drug Reactions Seen at a University Hospital Department of Dermatology

Abstract: Patients with suspected cutaneous adverse drug reactions are often referred to allergy clinics or departments of dermatology for evaluation. These patients are selected compared with patients identified in prospective and cross-sectional studies of hospital populations. This explains the observed variation in prevalence of specific reactions and of eliciting drugs. This study investigated the prevalence of cutaneous adverse drug reactions in a university hospital department of dermatology that is specially foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 19 publications
5
28
2
3
Order By: Relevance
“…But certain other studies have reported a higher incidence, 2.6% in a study conducted in North India [5] and 1.5% and 1.38% respectively in some other studies [6,7].The lower incidence of cADR in our study may be due to the fact that being a tertiary care centre only doubtful and serious cases had attended our hospital. Some studies had reported a higher frequency in women [8,9] whereas some other studies have noticed higher occurrence in men [10,11].…”
Section: Methodscontrasting
confidence: 52%
“…But certain other studies have reported a higher incidence, 2.6% in a study conducted in North India [5] and 1.5% and 1.38% respectively in some other studies [6,7].The lower incidence of cADR in our study may be due to the fact that being a tertiary care centre only doubtful and serious cases had attended our hospital. Some studies had reported a higher frequency in women [8,9] whereas some other studies have noticed higher occurrence in men [10,11].…”
Section: Methodscontrasting
confidence: 52%
“…[13] Few studies explored the rate of cADRs seen by a hospital dermatology department; cADRs accounted for 1.38% of all referrals to a university hospital department of dermatology in Denmark and 1.5% of total dermatology consultations seen at a hospital in Tunisia. [8,14] The lower rate of cADRs (0.86%) seen in our department was probably due to referral bias where only doubtful or serious cADRs were referred to us.…”
Section: Discussionmentioning
confidence: 92%
“…Most epidemiological studies analyzed the occurrence of cADRs in inpatients and revealed a wide variation in the prevalence rate which ranged from 0.36% to 12.2%. [5][6][7][8][9][10]12] A meta-analysis of 39 prospective studies from US hospitals showed that 15.1% of hospitalized patients had cADR. [13] Few studies explored the rate of cADRs seen by a hospital dermatology department; cADRs accounted for 1.38% of all referrals to a university hospital department of dermatology in Denmark and 1.5% of total dermatology consultations seen at a hospital in Tunisia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experience they are of little value in routine investigation of drug allergy [1,11]. Instead, patients are routinely instructed to contact the allergy clinic in case of delayed reactions to IDT and are questioned with regard to adverse reactions to skin tests when they return for the DCT or following the FC-DCT.…”
Section: Discussionmentioning
confidence: 99%